ATLAS OF LIGHT CURVES OF FAINT MIRA-TYPE STARS. STATISTICAL RELATIONS BETWEEN THE CHARACTERISTICS OF SMOOTHED PHASE LIGHT CURVES - Kudashkina, L. S.; Andronov, I. L. (Одеські астрономічні публікації, 2010)
We propose a set of the photometric parameters which could be useful for the classiffication of the pulsating Mira-type stars and related objects and determination of the EAGB and TPAGB stages of the stellar evolution. To solve this problem, the light curves of faint Mira-type stars and of the semi-regular variable V411 Sct were approximated using the program FDCN, which computes a trigonometric polynomial of a statistically optimal degree (I.L.Andronov, 1994, 2003). The at las of statistically optimal fits of the phase curves of 34 long-period is presented, based on digitized data from the scanned "Atlas" by P. Maffei and G.Tosti (http://astro.fisica.unipg.it/atlasmaffei/main.htm). Some statistical relations between the parameters of the trigonometrical polynomial approximation of the phase curve are analyzed. for an additional criterion of detailed classiffication of long-perodic variables, we used various parameters, e.g. "period", "amplitude", "asymmetry", "slope of the ascending branch", "characteristic time of brightening by 1m": Discussion of the results is presented.